Spatial Access to Continuous Maternal and Perinatal Health Care Services in Low-Resource Settings: Cross-Sectional Study - Qin Li; Elsa Kanduma; Isaías Ramiro; Dong (Roman); Rosa Marlene Manjate Cuco; Eusebio Chaquisse; Yili Yang; Xiuli Wang; Jay Pan (JMIR Publications, 2024)
BackgroundMaternal and perinatal health are fundamental to human development. However, in low-resource settings such as sub-Saharan Africa (SSA), significant challenges persist in reducing maternal, newborn, and child mortality. To achieve the targets of the sustainable development goal 3 (SDG3) and universal health coverage (UHC), improving access to continuous maternal and perinatal health care services (CMPHS) has been addressed as a critical strategy. ObjectiveThis study aims to provide a widely applicable procedure to illuminate the current challenges in ensuring access to CMPHS for women of reproductive age. The findings are intended to inform targeted recommendations for prioritizing resource allocation and policy making in low-resource settings. MethodsIn accordance with the World Health Organization guidelines and existing literature, and taking into account the local context of CMPHS delivery to women of reproductive age in Mozambique, we first proposed the identification of CMPHS as the continuum of 3 independent service packages, namely antenatal care (ANC), institutional delivery (ID), and postnatal care (PNC). Then, we used the nearest-neighbor method (NNM) to assess spatial access to each of the 3 service packages. Lastly, we carried out an overlap analysis to identify 8 types of resource-shortage zones. ResultsThe median shortest travel times for women of reproductive age to access ANC, ID, and PNC were 2.38 (IQR 1.38-3.89) hours, 3.69 (IQR 1.87-5.82) hours, and 4.16 (IQR 2.48-6.67) hours, respectively. Spatial barriers for women of reproductive age accessing ANC, ID, and PNC demonstrated large variations both among and within regions. Maputo City showed the shortest travel time and the best equity within the regions (0.46, IQR 0.26-0.69 hours; 0.74, IQR 0.47-1.04 hours; and 1.34, IQR 0.83-1.85 hours, respectively), while the provinces of Niassa (4.07, IQR 2.41-6.63 hours; 18.20, IQR 11.67-24.65 hours; and 7.69, IQR 4.74-13.05 hours, respectively) and Inhambane (2.69, IQR 1.49-3.91 hours; 4.43, IQR 2.37-7.16 hours; and 10.76, IQR 7.73-13.66 hours, respectively) lagged behind significantly in both aspects. In general, more than 51% of the women of reproductive age, residing in 83.25% of Mozambique's land area, were unable to access any service package of CMPHS in time (within 2 hours), while only about 21%, living in 2.69% of Mozambique's land area, including Maputo, could access timely CMPHS. ConclusionsThe spatial accessibility and equity of CMPHS in Mozambique present significant challenges in achieving SDG3 and UHC, especially in the Inhambane and Niassa regions. For Inhambane, policy makers should prioritize the implementation of a decentralization allocation strategy to increase coverage and equity through upgrading existing health care facilities. For Niassa, the cultivation of well-trained midwives who can provide door-to-door ANC and PNC at home should be prioritized, with an emphasis on strengthening communities' engagement. The proposed 2-step procedure should be implemented in other low-resource settings to promote the achievement of SDG3.